1981
DOI: 10.1128/iai.33.3.801-805.1981
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity and reduced periodontal bone loss in Eikenella corrodens-monoassociated rats

Abstract: Germfree Sprague-Dawley rats monoassociated with Eikenella corrodens exhibited alveolar bone loss. This progressive bone loss occurred over a period of weeks, during which time the hosts developed an immune response toward the infective microorganism. By means of repeated bacterial vaccination resulting in elevated serum antibody titers, reduced bone loss was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In our laboratory, Johnson et al (1978) observed accelerated bone destruction in genn-fi^e, irradiated, immunosuppressed rats monoinfected with Eikenella corrodens as compared to nonimmunosuppressed controls, suggesting that absence of immune response does not prevent bone resorption. In agreement with these, our findings indicate that the lack of proper immune response permits the alveolar bone resorption in the mono-infected germ-free rat system (Johnson et al 1978, Behling, Pham & Nowotny 1979 while active immunization prevents its development (Behling et al 1981). Results of other laboratories support the protective effect of immunization (Guggenheim & Schroeder 1974, Rylander, Lindhe & Ahlstedt 1976, Crawford, Taubman & Smith 1978b.…”
Section: Introducttonsupporting
confidence: 88%
“…In our laboratory, Johnson et al (1978) observed accelerated bone destruction in genn-fi^e, irradiated, immunosuppressed rats monoinfected with Eikenella corrodens as compared to nonimmunosuppressed controls, suggesting that absence of immune response does not prevent bone resorption. In agreement with these, our findings indicate that the lack of proper immune response permits the alveolar bone resorption in the mono-infected germ-free rat system (Johnson et al 1978, Behling, Pham & Nowotny 1979 while active immunization prevents its development (Behling et al 1981). Results of other laboratories support the protective effect of immunization (Guggenheim & Schroeder 1974, Rylander, Lindhe & Ahlstedt 1976, Crawford, Taubman & Smith 1978b.…”
Section: Introducttonsupporting
confidence: 88%
“…In particular, it is noteworthy that rats immunized with 10'" cells and having a high serum antibody level against B. gingivalis fitnbriae at the time of infection did not show evidence of periodontal destruction by any ofthe 4 tnethods. Cell-tnediated immunity was not assayed in this study, but in a previous investigation no obvi-ous association was found between disease severity and spleen cell blastogenesis to the microorganism used for immunization and infection (2).…”
mentioning
confidence: 74%
“…It was suggested that these findings support a hypersensitivity reaction in the progression of disease; however, under normal conditions suppressor mechanisms maintain a stable host-parasite interaction. Parenteral immunization of rats with whole bacterial sonicate elicited significantly elevated antibodies in a germ-free rat model system that developed alveolar bone loss following monoassociation with E. corrodens (5). The immunized rats showed less bone loss than infected controls.…”
Section: Actinomycetemcomitans-sensitized T Cells Transferred Into Otmentioning
confidence: 97%
“…gingivulis in- T cell clones increased antibody Protection Burckhardt et al (11) Immunized l? gingivalis Protection Behling et al (5) Immunized (17) immunized mice with heatkilled l? gingivalis A7A1-28, €?…”
Section: Actinomycetemcomitans-sensitized T Cells Transferred Into Otmentioning
confidence: 99%